EC competition law and the regulation of passive investments among competitors - Ezrachi, A; Gilo, D (2006)
Passive holdings and cross-investments among competing companies are common phenomena in the modern marketplace. Yet under certain market conditions such investments may cause anticompetitive effects. This article explores the economic effects of passive investments and their regulation under European competition law. The article identifies a range of transactions that potentially affect competition; however they remain unchallenged under current regulation. Subsequently, the article explores the possibility of applying the European Merger Regulation to these transactions. © 2006 Oxford University Press.